INTEGRATION OF SOCIO-SCIENTIFIC ISSUES IN CHEMISTRY LEARNING OUTCOME TESTS TO MEASURE HIGH SCHOOL STUDENTS SCIENTIFIC EXPLANATION SKILLS - Hanan, Annida Fadlila; Dra. Susila Kristianingrum, M.Si (UIN Mataram, 2024)
Socio-scientific issues (SSI) are controversial issues related to socio-science. SSI can be integrated into chemistry learning outcome tests to measure students’ scientific explanation skills. This research aimed to develop a socio-scientific issues based test to measure the scientific explanation skills of high school students in acid-base material. The development model used is an exploratory mixed method. Qualitative data were collected through needs analysis, literature studies for references for initial test development, expert feasibility test, and usability feasibility test (qualitative) to obtain input from experts and reviewers. The results of the quantitative test showed that the test developed has an ideal percentage of 87% (Very Good) according to the reviewer and 71% (Good) according to the students. The number of valid items based on the item fit test was 15. A total of 10 questions have the discrimination category very good, 3 questions were good, 1 question was fair, and 1 question was not able to discriminate. The difficulty level test revealed that 26,67% of the questions were very difficult, 26,67% of the questions were difficult, 33,33% of the questions were easy, and 13,33% of the questions were very easy. The Cronbach Alpha reliability value of the test was 0.77, categorized as good.